Bioactive compounds of oils extracted from fruits seeds obtained from agroindustrial waste. Issue 4 (6th October 2016) - da Silva, Ana Carolina; Jorge, Neuza
Abstract : This study aimed at evaluating the oils extracted from seeds originating from agroindustrial wastes, in order to identify the presence of bioactive compounds. The oils extracted from seeds of apple, citron, grape, guava, kumquat, mangaba, mango, melon, orange, papaya, passion fruit, pumpkin, soursop, strawberry, and tomato were studied. Therefore, determination of fatty acid profile, triglycerides, composition of tocopherols, phytosterols and phenolic compounds, and total carotenoids was performed in the oils. Strawberry seed oil stood out for its high content of linolenic acid (31.5%), which is classified as essential fatty acid, and also for its high content of phenolic compounds, compared to the other samples. The concentrations of tocopherols ranged from nd (not detected), in kumquat seed oil, to 534.53 mg/kg, in apple seed oil. The main phytosterol found among the samples was β‐sitosterol. Practical applications: The analyses accomplished indicate that these oils can be a new source of oils for human consumption. The information presented might be directly used for developing of functional foods, as well chemical, pharmaceutical, and cosmetic industries. This study aimed at evaluating the oils extracted from seeds originating from agroindustrial wastes. Determination of fatty acid profile, composition of tocopherols, phytosterols and phenolic compounds, and total carotenoids was performed in the oils extracted from seeds of apple, citron, grape, guava, kumquat, mangaba, mango, melon, orange, papaya, passion fruit, pumpkin, soursop, strawberry, and tomato. Abstract : This study aimed at evaluating the oils extracted from seeds originating from agroindustrial wastes. Determination of fatty acid profile, composition of tocopherols, phytosterols and phenolic compounds, and total carotenoids was performed in the oils extracted from seeds of apple, citron, grape, guava, kumquat, mangaba, mango, melon, orange, papaya, passion fruit, pumpkin, soursop, strawberry, and tomato.